2001
DOI: 10.1021/om0101902
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Neopentylindium(III) Derivatives with Isopropylphosphorus Compounds

Abstract: A 1:1 mixture of In(CH2CMe3)3 and HP(i-Pr)2 at room temperature undergoes a very slow hydrocarbon elimination reaction to form [(Me3CCH2)2InP(i-Pr)2]2 and neopentane. The indium phosphide [(Me3CCH2)2InP(i-Pr)2]2 has also been prepared by reacting KIn(CH2CMe3)3H with ClP(i-Pr)2 in pentane. When pentane solutions of these reagents were combined at −78 °C and then maintained at ∼20 °C for 2 days, [(Me3CCH2)2InP(i-Pr)2]2, (Me3CCH2)3In·P(H)(i-Pr)2, (Me3CCH2)3In·P2(i-Pr)4, (Me3CCH2)3In·P(CH2CMe3)(i-Pr)2, H2, indium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…17 kcal mol -1 , tends to bear out this view. 124 Calculations on parent mono-, di-, and triamidoborane, alane, gallane, and indane and their silyl substituted congeners provided similar M-N bond lengths and showed that, although π-bonding plays a significant role in the structures of amido boranes, it is weak in the heavier group 13 congeners. The calculations also showed that negative hyperconjugative interactions are significant when the amido groups are rotated out of the metal coordination plane.…”
Section: Dianions Of Formula [R 2 Eder 2 ] 2-(e ) Group 13 Element)mentioning
confidence: 55%
See 1 more Smart Citation
“…17 kcal mol -1 , tends to bear out this view. 124 Calculations on parent mono-, di-, and triamidoborane, alane, gallane, and indane and their silyl substituted congeners provided similar M-N bond lengths and showed that, although π-bonding plays a significant role in the structures of amido boranes, it is weak in the heavier group 13 congeners. The calculations also showed that negative hyperconjugative interactions are significant when the amido groups are rotated out of the metal coordination plane.…”
Section: Dianions Of Formula [R 2 Eder 2 ] 2-(e ) Group 13 Element)mentioning
confidence: 55%
“…Its structure may be compared with the behavior of TlN(SiMe 3 ) 2 , which has a dimeric structure in which two Tl + ions symmetrically bridge two N(SiMe 3 ) 2 ligands in the solid state but was shown by gas electron diffraction (ged) to have a monomeric structure in the vapor phase. 124 The corresponding structurally characterized group 13 element derivatives of the heavier pnictogens are given in Table 7. 108,[125][126][127][128][129][130][131][132][133][134][135][136][137] Most derivatives involve bonding to phosphorus.…”
Section: Dianions Of Formula [R 2 Eder 2 ] 2-(e ) Group 13 Element)mentioning
confidence: 95%
“…For related dimeric phosphanylindanes, see: Alcock et al (1989); Wells et al (1992); Aitchison et al (1989); Beachley et al (1987Beachley et al ( , 1993Beachley et al ( , 1995Beachley et al ( , 2001; Culp et al (1997); Malik et al (1996); Thomas et al (2002); Wells et al (1993); von Hanisch (2001). For related trimeric phosphanylindanes, see: Burns et al (1994); Werner & Neumü ller (1996); Banks et al (1991).…”
Section: Related Literaturementioning
confidence: 99%
“…Phosphanylindanes [R 2 InPR′ 2 ] n form dimeric or trimeric structures in the solid state via intermolecular In-P coordinate bonding interactions (Beachley et al, 2001;Werner & Neumuller 1996). Dimeric structures feature distorted tetrahedral geometries at indium and phosphorus, and planar four-membered In 2 P 2 ring cores.…”
Section: S1 Commentmentioning
confidence: 99%